Fostering Ethnomathematics in Projective Geometry: A Hypnoteaching Framework for Effective Distance Learning - Jafaruddin, Jafaruddin; Chen, Wen-Haw (Southeast Asian Mathematics Education Journal, 2023)
This  study  evaluated  the  impact  of  integrating  students'  cultural  backgrounds  into  online learning to improve understanding and participation. It employed "Simple House Theory" and projective  geometry  in  designing  traditional  houses  to  make  complex  mathematical  concepts relatable. The Ethnomathematics project and the Hypnoteaching model were two instructional strategies  that  successfully  enhanced  active  student  participation  in  distance  learning.Data was  collected  from  a  joint  course  between Universitas  Negeri  Makassar  (UNM  Makassar), Indonesia,  and Tunghai  University,  Taiwan.  The  study  involved  36  students:  20  from  UNM Makassar’s international mathematics education program (Group I) and 16 from Tunghai University’s applied mathematics department (Group II). Various tools like surveys, tests, and projects  were  employed  for  data  collection.  The  survey  had  23  Likert-scale  questions, allowing a thorough evaluation of student feedback. Quantitative analysis of this data revealed that   incorporating   the Ethnomathematics   projects   and   Hypnoteaching   model   into   the curriculum significantly  increased  student  engagement  in  remote  learning.  This  was  further evidenced  by  improved  student  performance  in  project  work.  The  research  underscores  the benefits of culturally relevant teaching  methods in enhancing engagement and understanding in  online  mathematics  education.  It  highlights  the  effectiveness  of  embedding  local  cultural elements into online learning environments, creating more engaging and relatable experiences. The  study  suggests  the  potential  of  these  approaches  in  other  educational  contexts  and disciplines for future research.